1993
DOI: 10.1002/path.1711690311
|View full text |Cite
|
Sign up to set email alerts
|

Manganese superoxide dismutase content and localization in human thyroid tumours

Abstract: Manganese-containing superoxide dismutase (Mn-SOD) content and its immunohistochemical localization in human thyroid tumours and some other thyroid diseases were examined and compared with adjacent normal thyroid tissue. Enzyme-linked immunosorbent assay (ELISA) was used in this study for the measurement of Mn-SOD. The content of Mn-SOD tended to increase in diffuse hyperplasia, adenomatous goitre, and follicular adenoma. In papillary carcinoma, it was significantly higher than in adjacent normal thyroid tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 19 publications
5
28
1
Order By: Relevance
“…However, the role of MnSOD in tumours is more complicated than originally assumed. Recent studies have detected high MnSOD levels in colon cancer (Nakano et al, 1996), thyroid cancer (Nishida et al, 1996) and tumours of central nervous origin (Cobbs et al, 1996;Landriscina et al, 1996), and our data on M38K (Kinnula et al, 1996). Tumours may have high immunoreactive protein without elevated enzyme activity, but our mesothelioma cells also demonstrated elevated specific activity of MnSOD (Kinnula et al, 1996).…”
Section: Discussionsupporting
confidence: 60%
“…However, the role of MnSOD in tumours is more complicated than originally assumed. Recent studies have detected high MnSOD levels in colon cancer (Nakano et al, 1996), thyroid cancer (Nishida et al, 1996) and tumours of central nervous origin (Cobbs et al, 1996;Landriscina et al, 1996), and our data on M38K (Kinnula et al, 1996). Tumours may have high immunoreactive protein without elevated enzyme activity, but our mesothelioma cells also demonstrated elevated specific activity of MnSOD (Kinnula et al, 1996).…”
Section: Discussionsupporting
confidence: 60%
“…These findings suggest that the Mn-SOD gene could behave as a potential tumor suppressor gene [10, 11, 12, 13, 14, 15, 16]. Conflicting reports, however, have shown that higher Mn-SOD expression is present in the sera or tumor tissues of patients with cancers of the ovary, thyroid, uterus, brain and some leukemias [17, 18, 19, 20, 21]. Thus, the significance of Mn-SOD expression in malignant tumors remains controversial and requires further study.…”
Section: Introductionmentioning
confidence: 82%
“…The concept of ‘tumor suppression’ function of Mn-SOD has recently been challenged by showing higher Mn-SOD expression and/or activity in cancer cells [17, 18, 19, 20, 21]. For example, Izutani et al [31]examined the expression of Mn-SOD mRNA in gastric carcinomas by RT-PCR and showed significantly higher levels of Mn-SOD expression in cancer tissue than in noncancerous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have shown that MnSOD is lower in malignant tissue and malignant cells than in their non-malignant counterparts (Sun, 1990), MnSOD has been shown to be high in human thyroid tumours (Nishida et al, 1993), human renal adenocarcinoma of granular cell type (Oberley et al, 1994), human brain tumours (Cobbs et al, 1996) and human malignant mesothelioma (Kahlos et al, 1998) as compared to corresponding non-malignant control tissues. The mesothelioma tumour biopsies and cell lines used in our studies are from untreated mesothelioma patients.…”
Section: Discussionmentioning
confidence: 98%